Nuno Portas and the Spanish influence on the definition of housing policies in Portugal in the period of democratic transition - Pinto, P. T.; Brandão, A.; Lopes, S. S. (Crossing frontiers: International networks of Spanish architecture (1939-1975), 2021)
Taking the housing crisis and the SAAL program as a central interest point of architects and sociologists in the aftermath of the Portuguese revolution, this chapter tracks the influence of Spanish architecture in Portugal and the relations of Portuguese and Spanish architects, signaling the main role of Nuno Portas. It begins by introducing the background of the architecture exchange between Portugal and Spain, since the 1960’s, through the diffusion and interchange activities of Nuno Portas (section 2). It continues to discuss the role of architects on urban change during the revolutionary process from the viewpoint Joan Antonio Solans experiences and writings (Section 3). Then it takes on the social movements debate with Manuel Castells reflections and writings about the new housing policies and experiences (Section 4). Finally, a short reflection on the interchange of ideas and experiences between Portugal and Spain in presented in the conclusion (Section 5).